EFEKTIVITAS MACAM PUPUK KANDANG DAN JARAK TANAM PADA HASIL TANAMAN OKRA (Abelmaschus esculentus, L. Moench) - Siti Hadiyati Arifah; Murti Astininngrum; Yulia Eko Susilowati (JURNAL VIGOR, 2019)
Research on the Effectiveness of Kinds of Manure and Plant Spacing on the yield of Okra Plants (Abelmoschus esculentus, L. Moench) was conducted from May until August 2018 Kanci II Sub village, Salamkanci Village, District Bandongan, Magelang. The Altitude is 410 m and the soil pH is 6,1. The method was factorial, arranged in a randomized complete block design (RCBD) with three block. The first factor was kind of manure, chicken manure and goat manure. The second factor was plant spacing of 50 cm x 40 cm; 50 cm x 50 cm; 50 cm x 60 cm and 50 cm x 70 cm. The results showed that giving manure yielded the highest yield on height of plants, number of leaves, number of fruits per plant, number of fruits per m2, fruit weight per plant, fruit weight per m2, fresh weight of stover per plant and harvest index. The spacing of 50 cm x 70 cm gives hight yield on the weight of fresh stover per plant. Different types of manure at different spacing gave the same results on all parameters observed.